Potential Color Change in Ceramic-based Restorations - Lia Kartika Wulansari; Prasetyo, Fernandy Hartono (Indonesia Prosthodontic Association, 2024)
Ceramic materials are among the materials used in restorative dentistry. They are widely used for restoration in esthetically demanding areas. Consequently, this material requires excellent color stability on top of adequate strength and good biocompatibility to achieve prosthodontic treatment success, especially in the aesthetic aspect. Lithium disilicate and zirconia are two popular ceramic materials used in dentistry mainly due to their translucency and strength. This scoping review aims to evaluate the potential for ceramic materials, mainly lithium disilicate and zirconia, to change colors after thermocycling with or without the staining process. Thermocycling is a laboratory method used to simulate daily oral use in relatively short periods. Twelve (12) articles extracted from 172 articles in 3 database resources based on the inclusion and exclusion criteria (journal articles in English from 2017-2021 that evaluate the color change in ceramic materials after thermocycling with or without staining process) are reviewed for the color change of several ceramic restoration materials. All materials generally show color change; lithium disilicate and zirconia-reinforced lithium silicate show the slightest color change compared to zirconia, feldspathic, or hybrid ceramic materials. Glazed materials offer better color stability compared to polished materials. Several staining solutions significantly contribute to the color change: coffee, tea, and wine. The thickness of materials and adhesive cement may also contribute to the color change of ceramic materials. In conclusion, all materials show color change after the thermocycling process; however, only hybrid ceramics show a level of color change that is above the tolerated limit. Keywords: ceramics, color change, lithium disilicate, thermocycling, zirconia